Evaluating the use of unassimilated bio‐anode with different exposed surface areas for bioenergy production using solar‐powered microbial electrolysis cell. (6th August 2021) - Muddasar, Muhammad; Liaquat, Rabia; Abdullah, Ali; Khoja, Asif Hussain; Shahzad, Nadia; Iqbal, Naseem; Ali, Muhammad Ishtiaq; Uddin, Azhar; Ullah, Sami
Summary: The microbial electrolysis cell (MEC) is an emerging technology for bioenergy production using organic wastewater. Normally, a preassimilated bio‐anode is utilized by the MEC to break down the organic content, but the formation and assimilation of microbial community at the anode surface is a time‐consuming process. This study utilized a novel unassimilated Ni‐foam anode for the first time in solar‐powered MEC for bioenergy production. Synthetic dairy manure wastewater (SDMW) was used both as substrate and an inoculum in the solar‐powered tubular MEC. The impacts of the exposed surface area of the bio‐anode on bioenergy production were evaluated by utilizing two different separation techniques (rate‐limited bio‐anode – MEC and fully exposed bio‐anode ‐ MEC). The former technique achieves a maximum methane production rate of 30.35 ± 0.03 mL/L, 14.2% more than that achieved by the later mentioned technique (26.4 ± 0.05 mL/L). Hydrogen production was approximately 800 ± 5 mm 3 in both experimentations. The maximum generated current in the rate limited bio‐anode – MEC was 35.5 mA. Scanning electron microscope images confirmed the formation of rod‐shaped along with round‐shaped microbial communities on the anode surface, and, interestingly, round‐shaped bacteria were also grown on the cathode surface. The bioenergy (H2 and CH4 ) produced using SDMW within first 13 days of operation, along with the formation of a microbial community, was a significant success in this area and has opened up many research opportunities for producing instant bioenergy from organic waste. Abstract : This study utilized a novel unassimilated Ni‐foam anode in solar powered‐MEC for bioenergy production. The bioenergy (H2 and CH4 ) produced using synthetic dairy manure wastewater within first 13 days of operation was a breakthrough in this field. SEM images confirmed the growth of microbial community responsible for the decomposition of organic substrate on the anode surface